ChemInform Abstract: Solid‐State Syntheses and Single‐Crystal Characterizations of Three Tetravalent Thorium and Uranium Silicates. Issue 7 (29th January 2015) - Jin, Geng Bang; Soderholm, L.
Abstract Colorless crystals of ThSiO4 (I) and (Ca0.5Na0.5) 2NaThSi8O20 (II) are prepared by solid state reactions of ThO2, CaSiO3, and Na2WO4 (evacuated silica ampoules, 1073 K, 140 h).